Urgency of the Malay Wedding Reception in Kepulauan Riau Based on Al-Maṣlaḥah Asy-Syathibi Perspective - Saiin, Asrizal; Umar, M. Hasbi; Badarussyamsi, Badarussyamsi; Radiamoda, Anwar M. (An-Nida', 2023)
A wedding reception in the Malay wedding tradition absolutely must be carried out by the Malay community in the Kepulauan Riau, because there are moral sanctions if someone does not follow the applicable customary law. Apart from that, there is a doctrine for the Malay community in Kepulauan Riau, that a wedding reception is important to hold, if a wedding reception is not held, then one's wedding procession will not be complete. Complexity in these problems often divert the value of the relationship between custom and religion, especially Islam, within the scope of sharia. Starting from the idea that in Islam, everything must be seen for its benefit, this research uses an approach al-Maṣlaḥah Ash-Shatibi. This research uses a type of field research with the nature of descriptive qualitative research. In this research the data used is primary data and secondary data. Primary data comes from data obtained through observation, interviews and documentation. Meanwhile, secondary data comes from internet sites, literature and other media. At the data processing stage there are three activities carried out, namely: editing, coding and tabulation. The results of this research show that if viewed based on al-Maṣlaḥah perspective, Malay wedding reception in Kepulauan Riau is something special taḥsiniyyah. This is because the traditional Malay wedding procession in Kepulauan Riau is only a support for a person's advancement in society and is simply a form of obedience. Abstrak: Resepsi pernikahan dalam tradisi perkawinan melayu mutlak harus dilaksanakan oleh masyarakat melayu di Kepulauan Riau, karena adanya sanksi moral apabila seseorang tidak megikuti hukum adat yang berlaku. Selain itu juga, terdapat doktrin bagi masyarakat melayu di Kepulauan Riau, bahwa resepsi pernikahan menjadi penting untuk dilaksanakan, jika resepsi pernikahan tidak dilaksanakan, maka belum sempurna prosesi pernikahan seseorang. Kompleksitas di dalam problematika tersebut sering kali mengalihkan nilai keterkaitan antara adat dan agama khususnya Islam dalam lingkup syariah. Berangkat dari pemikiran bahwa dalam Islam, segala sesuatu harus dilihat kemaslahatannya, dalam penelitian ini dengan pendekatan al-Maṣlaḥah asy-Syathibi. Penelitian ini menggunakan jenis studi lapangan (field research) dengan sifat penelitian kualitatif deskriptif. Dalam penelitian ini data yang digunakan adalah data primer dan data sekunder. Data primer berasal dari data yang diperoleh melalui observasi, wawancara, dan dokumentasi. Sedangkan data sekunder bersumber dari situs internet, kepustakaan dan media lainnya. Pada tahap pengolahan data ada tiga kegiatan yang dilakukan, yaitu: penyuntingan (editing), pengkodean (coding) dan tabulasi (tabulating). Hasil dari penelitian ini diketahui bahwa jika ditinjau berdasarkan perspektif al-Maṣlaḥah, resepsi pernikahan melayu di Kepulauan Riau merupakan sesuatu yang bersifat taḥsiniyyah. Hal ini karena prosesi pernikahan adat Melayu Kepulauan Riau, hanya menjadi suatu penunjang peningkatan seseorang dalam pergaulannya di masyarakat dan sebagai bentuk kepatuhan semata.